Search for Dark Matter Particles Produced in Association with a Top Quark Pair at √s=13 TeV; Physical Review Letters; Vol. 122, iss. 1 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2019, 2019)
Title screen